Extracellular vesicles derived from radioresistant oral squamous cell carcinoma cells contribute to the acquisition of radioresistance via the miR‐503‐3p‐BAK axis. Issue 14 (11th December 2021) - Yamana, Keisuke; Inoue, Junki; Yoshida, Ryoji; Sakata, Junki; Nakashima, Hikaru; Arita, Hidetaka; Kawaguchi, Sho; Gohara, Shunsuke; Nagao, Yuka; Takeshita, Hisashi; Maeshiro, Manabu; Liu, Rin; et al.
Abstract: Despite advancements in treatments, oral squamous cell carcinoma (OSCC) has not significantly improved in prognosis or survival rate primarily due to the presence of treatment‐resistant OSCC. The intercellular communication between tumour cells is a molecular mechanism involved in acquiring OSCC treatment resistance. Extracellular vesicles (EVs) and encapsulated miRNAs are important mediators of intercellular communication. Here, we focused on EVs released from clinically relevant radioresistant (CRR) OSCC cells. Additionally, we evaluated the correlation between miRNA expression in the serum samples of patients who showed resistance to radiotherapy and in EVs released from CRR OSCC cells. We found that EVs released from CRR OSCC cells conferred radioresistance to radiosensitive OSCC cells via miR‐503‐3p contained in EVs. This miR‐503‐3p inhibited BAK and impaired the caspase cascade to suppress radiation‐induced apoptosis. Furthermore, OSCC cells with BAK knockdown had increased radioresistance. Additionally, the expression of circulating miR‐503‐3p in patients with OSCC was correlated with a poor treatment response and prognosis of radiotherapy. Our results provide new insights into the relationship between EVs and the radioresistance of OSCC and suggest that the miR‐503‐3p–BAK axis may be a therapeutic target and that circulating miR‐503‐3p is a useful prognostic biomarker in the radiotherapy of OSCC.